Moving Forward from Project Failure: Negative Emotions, Affective Commitment, and Learning from the Experience - Shepherd, Dean A.; Patzelt, Holger; Wolfe, Marcus (Academy of Management Journal, 2011)
Project failures are common. We theorized and found that although time heals wounds (reduces the negative emotions from project failure), it heals differently depending on the strength of individuals' specific coping orientations. Further, wounds are shallower for those who perceive that their organization normalizes failure. We conjointly consider learning from failure and affective commitment to an organization as determining how individuals move forward from project failure. Findings suggest that studies framing moving forward solely as learning from failure will likely overstate the benefits of a “loss orientation” and understate the benefits of both a “restoration” and an “oscillation orientation.”